The fieldwork in/for/with ethnomathematics as a possibility of an affection research: Potencies of devir - De Matos Gondim, Diego [UNESP] (FapUNIFESP (SciELO), 2020)
With the objective of operating the fieldwork as a possibility of an affection research in/for/with Ethnomathematics, two experiments are performed in different research groups, namely: The anthropological-therapeutic experience of anthropologist Jeanne Favret-Saada, in a witchcraft community in Bocage, western France; and the cartographic experience of the author in a remaining community of quilombolas in the state of São Paulo. To affirm the invention of a body that slides between research and field, at least three types of devir are presented as an expression of their potency: To become a sorceress; to become a mandira; and to become a child. It is understood that all the experiences composed of the types of devir presented, express the fieldwork in/for/with Ethnomathematics as a possibility of an affection research.
O trabalho de campo na/para/com Etnomatemática como possibilidade de uma pesquisa afecção: Potências do devir
Keywords: (Mathematics) Education; Cartography; Ethnomathematics; Philosophy of Difference